Association between periodontitis and common variants in the promoter of the interleukin-6 gene - Nibali, L.; D’Aiuto, F.; Donos, N.; Griffiths, G.S.; Parkar, M.; Tonetti, M.S.; Humphries, S.E.; Brett, P.M. (Cytokine (Philadelphia, Pa.), 2009)
We recently reported an association between interleukin-6 ( IL6) polymorphisms (SNPs) and haplotypes and aggressive periodontitis (AgP). The aim of this study was to investigate this association in a larger cohort of subjects, affected by either aggressive or chronic periodontitis. Five IL6 SNPs were analyzed in 765 subjects (167 generalized aggressive periodontitis, 57 localized aggressive, 310 chronic periodontitis and 231 periodontally healthy). Among Caucasians ( n = 454) there were moderate associations for −1363T allele ( p = 0.011) and for −174GG and −1363GG genotypes with diagnosis of periodontitis (respectively, p = 0.044, OR = 1.6, 95% CI = 1.0–2.4, and p = 0.017, OR = 1.8, 95% CI = 1.1–2.8, adjusted for age, gender and smoking). Haplotypes containing the −174G>C, −1363G>T and −1480C>G polymorphisms were associated with diagnosis of periodontitis ( p = 0.02). Subgroup analysis by disease phenotype showed associations for the localized AgP (LAgP) group and −1480C>G and −6106A>T SNPs ( p = 0.007 and 0.010, respectively). Among Caucasians the genotypes IL6 −1480 CC and −6106 TT increased the adjusted OR for LAgP (OR = 3.09 and 2.27, respectively). This study supports the hypothesis that IL6 polymorphisms and haplotypes are moderately associated with periodontitis, possibly acting through influencing tissue levels of IL6. This association is stronger for LAgP than for other periodontal disease phenotypes.